2020
DOI: 10.1002/adma.202003913
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Chronic Inflammation for Inhaled Particles: the Impact of Material Cycling and Quarantining in the Lung Epithelium

Abstract: While new exciting applications arise from rapid development of new advanced materials, their lifecycle, from production, processing, to degradation or even combustion, may inevitably result in the release of particulate matter into the environment. [1-3] According to the Organisation for Economic Cooperation and Development (OECD) and the World Health Organization (WHO), inhalation of particulate matter, predominantly of anthropogenic origin, is associated with several million human deaths globally every year… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…The elevated fluorescence signal could be the first indication of the oxidative stress as a response to pathological conditions or toxic compounds [ 37 ] such as metal wear debris, just recently been found to induce the formation of reactive oxygen species [ 38 ]. Even more, in our latest study, metal oxide nanomaterial has also been found to be one of the key players in chronic inflammation [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The elevated fluorescence signal could be the first indication of the oxidative stress as a response to pathological conditions or toxic compounds [ 37 ] such as metal wear debris, just recently been found to induce the formation of reactive oxygen species [ 38 ]. Even more, in our latest study, metal oxide nanomaterial has also been found to be one of the key players in chronic inflammation [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we elucidated the mechanism how certain types of nanomaterials trigger previously unexplained chronic inflammation, based on which we designed an all-in-vitro test for its prediction. [19]…”
Section: An Example Of Detection Of Early Molecular Eventsmentioning
confidence: 99%
“…[11][12][13][14] To unravel fundamental molecular mechanisms of nanoparticle toxicity, it is crucial to identify the molecular events and their causal relationships, which heavily relies on monitoring nanoparticle localization and interaction with living cells in real-time. [15][16][17][18][19] One of the most powerful experimental techniques to study early molecular events including nanoparticle localization and interaction with living cells is fluorescence microscopy, especially its advanced super-resolution implementation with spatial and temporal resolution on the order of tens of nanometers and seconds, respectively. However, since most of the nanoparticles are not intrinsically fluorescent, such an experiment requires special preparation of the nanomaterial.…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 Exposure to TiO 2 NPs can cause lung inflammation and increased blood coagulation connected with cardiovascular diseases. 23 , 24 Although many possible adverse outcomes of TiO 2 NPs exposure are known, the molecular mechanisms of the nanotoxicity are uncertain. 29 , 30 To study the nanotoxicity mechanisms, a large number of experimental studies on model systems were carried out.…”
Section: Introductionmentioning
confidence: 99%